Peran Lembaga Pendidikan Non Formal Dalam Meningkatkan Kemampuan Membaca Dan Menulis Al-Qur’an Bagi Anak Putus Sekolah Di Desa Air Hitam Kecamatan Gebang - Indah Rafika, As’ad Badar, Usmaidar (Cybernetics: Journal Educational Research and Social Studies, 2022)
Research Title: Non-Formal Education of Al-Quran Reading and Writing in Air Hitam Village as an Effort to Eradicating Illiteracy in Gebang District. Problems found at the research location: Prevention of the loss of a generation that is unable to read and write the Qur'an really needs attention from all parties or stakeholders, especially in Gebang District in order to play a role in supporting learning activities to read the Qur'an as an effort to eradicate illiteracy in reading and writing Al-Quran. quran. One of them is by facilitating non-formal teachers, namely the Al-Quran Education Park (TPQ). The formulation of the problem in this study is 1. How is the condition of non-formal education specifically for reading and writing the Qur'an in Air Hitam Village, Kec. Gebang Kab. Langkat? 2. What is the role of non-formal Qur'anic reading and writing teachers in eradicating illiteracy in reading and writing the Qur'an in Air Hitam Village, Kec. Gebang Kab. Langkat? The conclusions in this study are: The ability of the younger generation in Air Hitam Village, Gebang District in 2021 in reading the Koran is included in the good category as obtained from research data in one of the Quran Education Parks in Air Hitam Village, namely TPQ Al-Hidayah.